Hak Paten Sebagai Objek Jaminan Fidusia - Putra Leonardo Sopamena; Merry Tjoanda; Yosia Hetharie (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: After the issuance of Law no. 24 of 2022 concerning the Creative Economy paving the way for the imposition of intellectual property rights as fiduciary guarantees, however, the mechanism and filing of patent rights are not explicitly explained in Law no. 42 of 1999 concerning Fiduciary Guarantees. The purpose of this study is to discover and study the determination of indicators for valuation of patents as objects of fiduciary guarantees and to review the mechanism for filing patents as objects of fiduciary guarantees. The method used in this study is normative juridical with statutory approach (statute approach) and the concept approach (conceptual approach). The legal materials used are primary legal materials, secondary which was analyzed qualitatively. The results of the study show that there are several indicators that can used to determine the value (valuation) of patent rights in the case of filing as fiduciary guarantees, namely the cost-based approach, the market approach (market based approach), and income approach (income based approach). The mechanism for submitting patent rights as objects of fiduciary guarantees is not voluntary specifically regulated in statutory provisions, but referring to Law Number 42 of 1999 concerning Fiduciary Guarantees in conjunction with Government Regulation Number 46 of 2020 regarding the Requirements and Procedures for Registration of Patent Transfers, then it can be done by filing an application for registration of patent transfer, as well as attaching supporting documents in the form of patent documents, copies of the agreement deed, power of attorney especially for applications submitted by proxy, proof of payment of the application fee, proof of payment of the annual fee for a patent, proof of recording of a patent license agreement has been given to other parties, a copy of the fiduciary guarantee certificate, and approval in writing from the fiduciary recipient if the right to a patent is used as the object of fiduciary guarantees, and a copy of the Presidential Regulation regarding the implementation of patents by the government.